Access to justice in the russian society: problems and contradictions - Nadezhda Afanasyevna Frolova; Ilya Mikhailovich Psarev (Вестник Майкопского государственного технологического университета, 2023)
The article deals with the problems of ensuring access of Russian citizens to justice. The relevance of the research is conditioned by the difficulties and inconsistency of the development of the judicial system in modern Russia, the existence and reproduction of illegal practices, the need to develop strategies to ensure access of any citizen to justice. Modernization of the entire judicial system is ultimately intended to help build a legal and democratic state in Russia. The purpose of the study was to analyze the attitude of the population to the Russian judicial system, as well as to identify the factors of access to justice in modern Russian society. The object of the study is the domestic judicial system, the subject is the access of Russian citizens to justice. The authors have used the method of secondary data analysis, as well as the method of mass survey (questioning). The number of the stratified sample was 460 people. The study has shown that, despite the ongoing reforms of the domestic judicial system, obstacles and restrictions in access of Russians to justice remain, which together determine a high level of public distrust of the court as a social institution and as a tool for solving problems. The authors have highlighted objective and subjective factors of access of Russian citizens to justice, it’s been concluded that ensuring the independence of courts and access of citizens to justice is associated with such social value as social justice.